IDENTIFIKASI MINERAL MAGNETIK PADA GUANO DI GUA BAU-BAU KALIMANTAN TIMUR MENGGUNAKAN SCANNING ELECTRON MICROSCOPE (SEM) - Tauhida Amalia Sari (PILLAR OF PHYSICS, 2014)
Change of environment of a cave can be seen from the presence of magnetic minerals in guano. In this research the magnetic minerals identified a Guano in Bau-Bau caves, East Kalimantan. This research aim to look the morphology, elemental composition, the kind of magnetic minerals, and how magnetic minerals transport into the cave. Magnetic minerals in guano identified by using Scanning Electron Microscope (SEM) that completed with Energy Dispersive Spectroscope (EDS). The result showed the morphology of magnetic minerals of the guano is oval and have some cracks, in addition to the grain size of magnetic minerals is multidomain, guano elements are Fe, O, Ti , Si, C, N, and Br. To determine the kind of magnetic minerals using Proust's Law. The results of calculation the kind of magnetic minerals that can form Hematite (Fe2O3), Magnetite (Fe3O4), Ilmenite (FeTiO3) and Rutile (TiO2). This is indicates the magnetic grains estimated come from the external environment and during the rainy, transportation into the cave. Keywords: Change of environment, magnetic minerals, guano, SEM